Drug Target Commons 2.0: a community platform for systematic analysis of drug–target interaction profiles. (13th September 2018) - Tanoli, ZiaurRehman; Alam, Zaid; Vähä-Koskela, Markus; Ravikumar, Balaguru; Malyutina, Alina; Jaiswal, Alok; Tang, Jing; Wennerberg, Krister; Aittokallio, Tero
Abstract: Drug Target Commons (DTC) is a web platform (database with user interface) for community-driven bioactivity data integration and standardization for comprehensive mapping, reuse and analysis of compound–target interaction profiles. End users can search, upload, edit, annotate and export expert-curated bioactivity data for further analysis, using an application programmable interface, database dump or tab-delimited text download options. To guide chemical biology and drug-repurposing applications, DTC version 2.0 includes updated clinical development information for the compounds and target gene–disease associations, as well as cancer-type indications for mutant protein targets, which are critical for precision oncology developments.